A Critique of Michèle Montrelay’s Theorizations of Masculine and Feminine Sexuality: On Psychoanalysis, Queer Theory, and the “Queer” Signifier - Nitzan Familia (EJP import test, 2023)
Summary: This article presents a critical reading and a reassessment of lesser-known psychoanalyst Michèle Montrelay’s innovative theorizations of human sexuality, examining Montrelay’s theorizations of masculine sexuality vis-à-vis the feminine and vice versa, and not in a particular hierarchical or gender-specific order. By following a psychoanalytical Freudian-Lacanian-Montrelayan framework while also incorporating elements from queer theory and (trans)gender studies that, at the same time, will be subjected to critical scrutiny in light of their potential limitations and inherent blind spots, I suggest that Montrelay’s conceptualizations of masculine and feminine sexuality can function as productive springboards to a contemporary exploration of human sexuality, jouissance (enjoyment) and desire, and their consequent linguistic signification via what I term the “queer” signifier in the latter part of this article. Transcending the limitations of identity politics, this article brings thus the discourses of psychoanalysis (especially in its Lacanian, linguistically inflected orientation) and queer theory into a theoretical, conceptual, and practical dialogue that is neither binary and normative nor even non-binary and nonnormative but semiotically singular. Finally, the “queer” signifier and an accompanying, “queer” modality of jouissance will be theorized as structurally homologous to feminine jouissance and feminine writing (écriture féminine).